Effect of Fermentation Using Lactobacillus plantarum A6 on the Physicochemical and Functional Properties of Precooked Sorghum bicolor and Voandzeia subterranea Blended Flour - Ntsamo, Thierry Marcel Beumo (Int J Food Sci, 2020)
The present study is aimed at producing Sorghum bicolor and Voandzeia subterranea complementary instant flour. The precooked sorghum and Bambara groundnut flours were mixed at different proportions (0 : 100, 25 : 75, 50 : 50, 75 : 25, and 100 : 0), hydrated with sterile distilled water (1 : 3, w:v), and fermented for 72 h/37°C using Lactobacillus plantarum A6 at 10(5) CFU/g. During the fermentation, samples were withdrawn for pH, titrable acidity, and microbial analyses. After fermentation, color, particle size, water absorption capacity (WAC), solubility index, least gelling concentration (LGC), and physicochemical and pasting properties were determined. The results showed that the fermentation significantly (p ≤ 0.05) decreased WAC, LGC, peak viscosity, final viscosity, breakdown, and pH, but increased the solubility index and titrable acidity of flours. The protein and carbohydrates contents as well as the color, particle size, and the setback after the cooking of the flour were not significantly affected by the fermentation. The flours ratio and fermentation also significantly decreased the total polyphenols, tannins, and phytate content of the samples. The fermented blended flour containing 25% precooked sorghum flour and 75% roasted Bambara flour (SVFP25) is a promising alternative as instant flour used for young children's nutrition.